Erchen decoction for hyperlipemia: Protocol for a systematic review and meta-analysis - Luo, Huan (Medicine (Baltimore), 2020)
BACKGROUND: Hyperlipidemia is a metabolic disease characterized by elevated levels of blood lipids and lipoproteins and a major pathogenic factor of atherosclerosis. In China, Erchen decoction (ECD) has been widely used to treat hyperlipidemia. However, there is no systematic review found. In order to evaluate the efficacy and safety of ECD in the treatment of hyperlipidemia, we need to conduct a meta-analysis and systematic evaluation. METHODS: We will enroll the randomized controlled trials (RCTs) evaluating the effectiveness and safety of ECD in the treatment of hyperlipidemia. Data come mainly from 4 Chinese databases (China national knowledge infrastructure, Wanfang, Chinese biomedical literature database, and VIP Database) and 4 English databases (Pubmed, Embase excerpt medica database, Cochrane Library, and Web of science). The enrollment of RCTs is from the starting date of database establishment till September 30, 2020. Low density lipoprotein cholesterol is considered as the main indicator of the dyslipidemia, while the serum concentrations of total cholesterol, triglyceride, high density lipoprotein cholesterol, apolipoprotein A, and apolipoprotein B are regarded as the secondary indicators. There are Safety indicators including liver enzyme, kidney function and fasting blood glucose. The work such as selection of literature, data collection, quality evaluation of included literature, and assessment of publication bias will be conducted by 2 independent researchers. Meta-analysis will be performed by RevMan 5.0 software. RESULTS: This study will provide high-quality evidence for the effectiveness and safety of ECD in the treatment of hyperlipidemia. CONCLUSION: The results of the study will help us determine whether ECD can effectively treat hyperlipidemia. ETHICS AND DISSEMINATION: This study does not require ethical approval. We will disseminate our findings by publishing results in a peer-reviewed journal. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/GZ69F